Evaluation of urban green space plant landscape quality in Zhengzhou city using the AHP-SBE method - Lingling Zhang; Yuan Gao; Qiutan Ren; Shidong Ge; Bingquan Wang; Chong Du; Yiping Liu; Dezheng Kong (PLoS ONE, 2025)
Urban green space plays a key role in urban ecosystems, and the quality of the landscape directly affects its ecological, aesthetic, and social functions. On the basis of field survey data from 349 sample sites in Zhengzhou City, this study constructed a comprehensive evaluation index system for plantscape and systematically evaluated 40 representative plantscape units using the hierarchical analysis method (AHP) and the scenic beauty estimation method (SBE). The results indicated that: (1) In the analysis of plant diversity, the diversity indices for trees, shrubs, and herbs in park green spaces were higher than those observed in other types of green spaces, with overall species richness reaching its highest level. (2) The results of the AHP comprehensive evaluation revealed that 10% of the samples were classified as high-quality (CEI ≥ 8 points), 57.5% as medium-to-high quality (6 ≤ CEI < 8 points), and 32.5% as medium or below (CEI < 6 points). The mean comprehensive scores across different green space types were ranked as follows: park green space> ancillary green space> protective green space> regional green space> plaza land. (3) The SBE evaluation results showed that only 40% of the samples achieved standardized scores above zero, while 60% scored below zero, indicating that the overall aesthetic quality of the planted landscapes was low and required optimization and improvement. (4) Spearman’s correlation analysis revealed that the AHP and SBE methods were highly consistent in terms of the ranking of the plant landscape units, and there was a significant positive correlation. This study combines quantitative evaluation and perceptual analysis methods to systematically reveal the characteristics and differences of plant escape among different types of green space in Zhengzhou City, which provides a theoretical basis and practical reference for the optimal design of plant escape in urban green spaces and the high-quality development of these spaces.